Ensuring Security for the Participants of Criminal Proceedings: Forensic Aspects - T. P. Matiushkova (Law and Safety)
One of the urgent tasks of criminalistics has been studied – the content and elements of forensic security of the participants of criminal proceedings have been determined. Traditionally, this activity is given considerable attention in the areas of criminal law, criminal procedure, as well as operative and search activities. The few works of criminalists mainly reflect the problems of anonymity of interrogating the witnesses, recommendations on tactical features of the interrogation and identification by the means of videoconference. Thus, there are currently no comprehensive studies of forensic aspects of ensuring security for the participants of criminal proceedings in Ukraine.